Network security - Perez, Andre (Networks and telecommunications series, 2014)
This book introduces the security mechanisms deployed in Ethernet, Wireless-Fidelity (Wi-Fi), Internet Protocol (IP) and MultiProtocol Label Switching (MPLS) networks.These mechanisms are grouped throughout the book according to the following four functions: data protection, access control, network isolation, and data monitoring. Data protection is supplied by data confidentiality and integrity control services. Access control is provided by a third-party authentication service. Network isolation is supplied by the Virtual Private Network (VPN) service.Data monitoring consists of applying rules to data in order to authorize its transfer or detect attacks. The chapters of the book cover cryptography, 802.1x mechanism, WPA mechanisms, IPSec mechanism, SSL/TLS/DTLS protocols, network management, MPLS technology, Ethernet VPN, firewalls and intrusion detection.--Back Cover.